Oral Tradition as a Medium of Inheriting Dramatari Wayang Topeng in Padepokan Seni Topeng Asmarabangun, Malang, Indonesia - Rahayuningtyas, Wida; Jazuli, Muhammad (Universitas Negeri Semarang, 2018)
Masked performance depicting various characters in Panji stories from Java is called Mask Puppet Dance-Drama (Dramatari Wayang Topeng or DWT for short). Panji stories consist of a collection of stories from the Kediri Kingdom themed heroism and love with Panji Asmarabangun and Dewi Sekartaji as the main characters. As the nation's cultural successor, many younger generations have not known the DWT performance. This can threaten the preservation of DWT as one of the nation's cultural heritages to be preserved. This study aimed to examine the process of the DWT inheritance in Asmarabangun Mask Art Gallery (Padepokan Seni Topeng Asmarabangun) through oral tradition. This research was based on the theory of social construction in which a process of meaning done by each individual to himself consists of the process of externalization, internalization, and objectivization. This study used a qualitative method. Data were obtained through observation, interviews, and documentary studies. The data were analyzed using Milles & Huberman's theory of data reduction, presentation and verification. The result of data analysis shows that oral tradition in DWT inheritance process occurs institutionally which requires a process of meaning making by every individual to himself which consists of externalization, internalization and objectivization process. In the process, people can learn about the material either directly or indirectly. People get information and interact to achieve certain goals. The tradition is inherited through the process of seeing, listening, and doing.